Systematic Review on the Use of Electroencephalogram in Detecting Work Fatigue - Gregory, Xavier; Anselm, Su Ting; Norsiah, Fauzan (2020)
Fatigue is one of the causes of occupational accidents and injuries especially among motor-vehicle users and those working in high risk jobs. For over many years there were attempts to quantify and objectify fatigue using an electroencephalogram (EEG). This systematic review is to the study protocols used and explore the results obtained to potentiate EEG’s ability as a fatigue prevention-screening tool. We used the PRISMA statement method to identify, collate and classify the articles for review from PubMed database. Three investigators, independently, using predefined criteria, assessed selection of the articles. They assessed its quality following a standard set of information too. Of the 962 articles, scanned only 24 articles met the criteria and showed acceptable quality. Almost no papers attended to the sampling method. However, their variable measurements and analysis are appropriate according to respective objectives. EEG recording is an objective assessment and readily duplicated but we could not perform meta-analysis due to inadequacy in standardized methods of data collection and analysis. Nevertheless, the EEG changes showed consistency in findings whereby theta and alpha wave bands are the best indicators in fatigue detection. Hence: making EEG a potential screening tool for fatigue.